Article III of the 1967 outer space treaty: Critical analysis - Ahmad Sharif, Haron; Loh, Ing Hoe; Maheran, Makhtar; Noor ‘Ashikin, Hamid (2015)
Article III of the 1967 Outer Space Treaty states that international law, including the Charter of the United Nations is applicable in the exploration of outer space. However, this article does not mention any limitation in the application of international law and Charter of the United Nations. The absent of limitation clause has caused the discrepancy of law in the application of the law of outer space and international law, including Charter of the United Nations in the exploration of outer space, because principles governing these two laws are different. Therefore, the authors will analyse the conflict of principles of law between law of outer space and international law. At the end of discussion the writer will suggest a solution to the problem that has been identified.